RANCANG DAN BANGUN APLIKASI HELPDESK SUPPORT SYSTEM BERBASIS WEBSITE PADA CV. GYAR INDONESIA - Jumjumi Asbullah; Triase (JURNAL ILMIAH BETRIK, 2023)
CV. Gyar Indonesia is a company engaged in technology that focuses on managing both web-based and Android/ios hardware and software. Many complaints or reports are still using whatsapp social media so that they are less effective in dealing with problems and making work twice and for that it is necessary to build a helpdesk support system to assist companies in handling reports or complaints and make it easier for administrators to manage and resolve these requests, so this system designed on a website basis so that it can be accessed by users from various locations and through various devices. The stages in the design of this application use UML (unified modeling language), and the codeigniter framework and MySql database so that this application is designed to increase efficiency in managing requests for help and problems from users, and ensure that problems are handled quickly and appropriately.